Pengaruh Kualitas Produk dan Harga terhadap Kepuasan Konsumen Honda Beat (Studi Kasus pada Pengguna Honda Beat di Kecamatan Medan Johor) - Fauzi Fauzi; Amrani Amrani (Universitas Islam Sumatera Utara, 2022)
The formulation of the problem in this study is how the influence of product quality on consumer satisfaction of Honda Beat in Medan Johor District, how the effect of price on consumer satisfaction of Honda Beat in Medan District of Johor, how the influence of product quality and price on consumer satisfaction of Honda Beat in Medan District of Johor. Based on the results of testing and analysis shows that there is a significant influence between product quality on consumer satisfaction, thus partially there is a positive and significant influence between product quality on consumer satisfaction. There is a significant effect between price on consumer satisfaction, because according to the results of statistical tests there is a positive effect of the price variable on the variable of consumer satisfaction. Thus partially there is a positive and significant influence between price on consumer satisfaction. Product quality and price simultaneously have an influence on consumer satisfaction.